A identidade no ensino-aprendizagem de português como língua de acolhimento: um estudo de caso com um migrante de língua materna asiática - Lívia Elisa Lemos Melo (2023)
This dissertation investigates a refugee student 's preparation for the ENEM (Exame Nacional do Ensino Médio) in the context of the language classes of the Pró-Imigrantes project, during the year 2021. This research aims to understand how the learner's imagined identity (NORTON, 2013) and the imagined community (ibidem) he wants to step into, influence his language learning process. For this purpose, the concepts of motivation and investment (ibidem) will also be explored. From that, the following specific objectives are developed: 1. By the interview with the student and the field journal, identify what is the student's imagined identity and which imagined community he wants to get into. 2. Comprehend in which way the imagined identity of a "purer" Brazilian and the imagined community of Brazilians who are able to access higher education at a public university interferes with the student's learning process; 3. Realize what are the student's motivations and needs concerning the learning of the Portuguese language for the ENEM exam. Founded on the theoretical framework of the identity studies (GOMES JUNIOR, 2015, GUALDA, 2020 e NORTON, 2013), of Portuguese as a welcoming Language (FERREIRA, et.al, 2019), of Indisciplinary Applied Linguistics (MOITA LOPES, 2006) and Translanguage (CANAGARAJAH, 2013) an ethnographic and interpretive qualitative research has been developed. This research is based on a case study with a stateless person who speaks an Asian language natively and is currently applying for asylum in Brazil. The data were generated by the audio recording of the classes and from a semi-structured interview and a field journal. The data analyses reveals that getting into a public university in Brazil represents more than an opportunity for integration, it's also seen as a tool for the imagined identity's negotiation, for him to become "more Brazilian" and that interferes directly with his motivation, and consequently on his investment at the language learning process. Access to higher education can also ensure access to some symbolic resources BOURDIEU, 1977) that can collaborate to create access to the imagined community (NORTON, 2013). It's also noticeable the need for a critical multicultural approach (KUBOTA, 1999) in the classroom, it's imperative to explore and comprehend the cultural differences in order to understand in which way those differences contribute to the student's meaning-making practices. Furthermore, critical multiculturalism (KUBOTA, 1999) allows the differences, such as racial ones, to be criticized and its consequences for the teaching-learning process to be comprehended. This approach also avoids specific cultural aspects to be reduced to stereotypes inside the learning environment. This work's development shows that the studies about identity and language learning can efficiently build a pedagogical practice that is also more effective and aims to better understand the learner's subjectivities.